A small electron beam ion trap/source facility for electron/neutral–ion collisional spectroscopy in astrophysical plasmas. (January 2018) - Liang, Gui-Yun; Wei, Hui-Gang; Yuan, Da-Wei; Wang, Fei-Lu; Peng, Ji-Min; Zhong, Jia-Yong; Zhu, Xiao-Long; Schmidt, Mike; Zschornack, Günter; Ma, Xin-Wen; Zhao, Gang
Abstract: Spectra are fundamental observation data used for astronomical research, but understanding them strongly depends on theoretical models with many fundamental parameters from theoretical calculations. Different models give different insights for understanding a specific object. Hence, laboratory benchmarks for these theoretical models become necessary. An electron beam ion trap is an ideal facility for spectroscopic benchmarks due to its similar conditions of electron density and temperature compared to astrophysical plasmas in stellar coronae, supernova remnants and so on. In this paper, we will describe the performance of a small electron beam ion trap/source facility installed at National Astronomical Observatories, Chinese Academy of Sciences.We present some preliminary experimental results on X-ray emission, ion production, the ionization process of trapped ions as well as the effects of charge exchange on the ionization.